Ocean acidification mediates photosynthetic response to UV radiation and temperature increase in the diatom Phaeodactylum tricornutum - Li, Y.; Gao, K.; Villafañe, Virginia Estela; Helbling, Eduardo Walter (Biogeosciences)
Increasing atmospheric CO 2 concentration is responsible for progressive ocean acidification, ocean warming as well as decreased thickness of upper mixing layer (UML), thus exposing phytoplankton cells not only to lower pH and higher temperatures but also to higher levels of solar UV radiation. In order to evaluate the combined effects of ocean acidification, UV radiation and temperature, we used the diatom Phaeodactylum tricornutum as a model organism and examined its physiological performance after grown under two CO 2 concentrations (390 and 1000 μatm) for more than 20 generations. Compared to the ambient CO 2 level (390 μatm), growth at the elevated CO 2 concentration increased non-photochemical quenching (NPQ) of cells and partially counteracted the harm to PS II (photosystem II) caused by UV-A and UV-B. Such an effect was less pronounced under increased temperature levels. The ratio of repair to UV-B induced damage decreased with increased NPQ, reflecting induction of NPQ when repair dropped behind the damage, and it was higher under the ocean acidification condition, showing that the increased pCO 2 and lowered pH counteracted UV-B induced harm. As for photosynthetic carbon fixation rate which increased with increasing temperature from 15 to 25 °C, the elevated CO 2 and temperature levels synergistically interacted to reduce the inhibition caused by UV-B and thus increase the carbon fixation. Fil: Li, Y. Xiamen University; China Fil: Gao, K. Xiamen University; China Fil: Villafañe, Virginia Estela. Fundación Playa Unión. Estación de Fotobiología Playa Unión; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Helbling, Eduardo Walter. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Fundación Playa Unión. Estación de Fotobiología Playa Unión; Argentina